An exploration of the facilitators and barriers experienced by Rehabilitation Care Workers in the provision of Speech-Language Therapy related services - Higgs, Salma (Department of Health and Rehabilitation Sciences, 2019)
Background: South Africa experiences a severe shortage of speech-language therapists (SLTs) which results in individuals requiring Speech-Language Therapy (SLT) services having to travel long distances or being placed on long waiting lists to access services. Rehabilitation Care Workers can assist with bringing this service closer to the communities they serve. It is important to explore the experiences of these individuals to ensure that they are adequately supported and skilled. The University of Cape Town (UCT) has been training Rehabilitation Care Workers (RCWs) since 2012, however to there is currently no empirical data documenting the facilitators and barriers experienced by RCWs in their work.